Enhancing Reporting of After Action Reviews of Public Health Emergencies to Strengthen Preparedness: A Literature Review and Methodology Appraisal. (17th September 2018) - Davies, Robert; Vaughan, Elly; Fraser, Graham; Cook, Robert; Ciotti, Massimo; Suk, Jonathan E.
ABSTRACT: Objective: This literature review aimed to identify the range of methods used in after action reviews (AARs) of public health emergencies and to develop appraisal tools to compare methodological reporting and validity standards. Methods: A review of biomedical and gray literature identified key approaches from AAR methodological research, real-world AARs, and AAR reporting templates. We developed a 50-item tool to systematically document AAR methodological reporting and a linked 11-item summary tool to document validity. Both tools were used sequentially to appraise the literature included in this study. Results: This review included 24 highly diverse papers, reflecting the lack of a standardized approach. We observed significant divergence between the standards described in AAR and qualitative research literature, and real-world AAR practice. The lack of reporting of basic methods to ensure validity increases doubt about the methodological basis of an individual AAR and the validity of its conclusions. Conclusions: The main limitations in current AAR methodology and reporting standards may be addressed through our 11 validity-enhancing recommendations. A minimum reporting standard for AARs could help ensure that findings are valid and clear for others to learn from. A registry of AARs, based on a common reporting structure, may further facilitate shared learning. ( Disaster Med Public Health Preparedness. 2019;13:618-625)